Yerba Maté and its impact on glycemic control and metabolic health: a systematic review and meta-analysis - Li, Daiping; Yue, Liantian; Peng, Xuchao; Chen, Ling; Lin, Taiping; Huang, Li; Liu, Yadong; Yue, Jirong; Huang, Xiaoli (Frontiers in Endocrinology, 2025)
PurposeYerba Maté, a traditional South American herbal infusion abundant in bioactive compounds, has been suggested to offer health benefits including lipid regulation and weight management. However, existing evidence remains inconclusive. This systematic review and meta-analysis seeks to conduct a comprehensive evaluation of the effects of Yerba Maté consumption on metabolic health outcomes using data from randomized controlled trials (RCTs).MethodsIn accordance with the PRISMA guidelines, a comprehensive systematic review and meta-analysis of RCTs was conducted, encompassing studies published up to January 2025. Studies were systematically retrieved from MEDLINE, EMBASE and The Cochrane Central Register of Controlled Trials without any language restrictions. The review included RCTs that evaluated the impact of Yerba Maté on metabolic health indicators. Meta-analyses were performed using Review Manager (RevMan 5.4) when two or more studies from the same comparator provided sufficient data. Quality assessment were assessed using the revised Cochrane risk-of-bias tool for randomized trials (RoB 2) tool. The overall quality of evidence was evaluated using the GRADE (Grading of Recommendations, Assessment, Development and Evaluations) method.ResultsA total of 1294 studies were initially identified, of which 13 RCTs met the inclusion criteria. The study population includes dyslipidemic volunteers, overweight and obese and non-dyslipidemic, normal-weight volunteers. The results with pre-diabetes patients suggest significant decreases in postprandial glucose (MD -12.76, 95% CI -16.78, -8.74; N = 2), HbA1c (MD -0.37, 95% CI -0.56, -0.18; N = 2), and the homeostatic model assessment index (HOMA index) (MD -0.24, 95% CI -0.37, -0.11; N = 2), though further research is needed to confirm these findings. No significant effects were found on triglycerides, total cholesterol, HDL-C, LDL-C, fasting glucose, fasting insulin, waist circumference, or BMI. Adverse events included mucosal irritation, insomnia, tachycardia, angina, headache, and gastrointestinal discomfort.ConclusionYerba Maté consumption may demonstrate favorable effects on glycemic control, though its impact on lipid profiles and weight management appears to be limited.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023369270.